Nutrient Composition Promotes Switching between Pellicle and Bottom Biofilm in Salmonella - Paytubi, Sonia; Cansado, Cintia; Madrid, Cristina; Balsalobre, Carlos (Frontiers in Microbiology, 2017)
Salmonella is one of the most frequently reported causes of food-borne illness worldwide. Non-typhoideal serovars cause gastroenteritis in humans. Salmonella can grow on surfaces forming biofilms, contributing to its persistence since biofilms are difficult to eradicate due to the high resistance to antimicrobials and disinfectants. It has been described that there are two crucial biofilm promoting factors in Salmonella: curli and cellulose. The expression of both factors is coordinately regulated by the transcriptional regulator CsgD. Most biofilm studies of Salmonella have been performed by growing bacteria in low osmolarity rich medium and low temperature (25ºC). In such conditions, the biofilm is formed at the air-liquid interface (pellicle biofilm). Remarkably, when Salmonella grow in minimal medium, biofilm formation switches from the air-liquid interface to the solid-liquid interface (bottom biofilm). In this report the switching between pellicle and bottom biofilm has been characterized. Our data indicate that curli, but not cellulose, is crucial for the formation of both kinds of biofilms. In minimal medium, conditions promoting formation of bottom biofilm, a high transcriptional expression of csgD and consequently of the genes involved in the synthesis of curli and cellulose was detected. The nutritional status of the cells seems to be pivotal for the spatial distribution of the biofilms formed. The data reported let us conclude that when bacteria is growing in minimal medium the presence of amino acids downregulates the expression of csgB and causes the switch between bottom and pellicle biofilm. The crosstalk between general metabolism and biofilm formation is also highlighted by the fact that the metabolic sensor cAMP modulates the type of biofilm generated by Salmonella. Moreover, cAMP regulates transcriptional expression of csgD and stimulates pellicle biofilm formation, suggesting that the physiological conditions define the type of biofilm formed by Salmonella. The consequences of the switching between pellicle and bottom biofilm during either infection or survival in natural environments remain undercover.